Interventions to reduce and prevent obesity in pre-conceptual and pregnant women: a systematic review and meta-analysis. - Maliha Agha; Riaz A Agha; Jane Sandall (PLoS ONE, 2014)
Background The increasing prevalence of obesity in pregnant women is associated with adverse maternal and neonatal outcomes, and increased costs to healthcare, the economy and broader society. Objectives To assess the efficacy of behavioural interventions for managing gestational weight gain (GWG) in the pre-conceptual and pregnancy period in overweight, obese and morbidly obese women. Search methods A search was performed for published studies in the English language, from date? 2000-31 December 2012 in five electronic databases; PubMed, Scopus, Cochrane Library, CINAHL and PsycINFO. Selection criteria Studies were included if they compared the efficacy or effectiveness of a particular behavioural intervention in pregnant or pre-conceptual women with standard maternity care. Studies that included women with co-morbid conditions such as diabetes mellitus and polycystic ovarian syndrome were excluded to help isolate the effect of the intervention. Results Fifteen studies involving 3,426 participants were included. One study (n = 692) focused on the pre-conceptual period and the remaining 14 (n = 2,734) in the pregnancy period. Pooled mean difference for GWG indicated a lower GWG in the intervention groups when compared to standard maternity care groups (n = 1771, mean difference (MD) -1.66 kg, 95% CI -3.12 to -0.21 kg). With respect to the types of participants, considerable heterogeneity between studies was shown in the obese subgroup [Tau(2) = 15.61; Chi(2) = 40.80, df = 3 (P<0.00001); I(2) = 93%]. Conclusions Behavioural interventions in pregnancy may be effective in reducing GWG in obese women without comorbid conditions, but not overweight or morbidly obese women. Behavioural interventions had no effect on postpartum weight loss or retention, gestation week of delivery and infant birth weight in overweight, obese and morbidly obese women.